Pattern formation in thin polymeric films via electrohydrodynamic patterning. Issue 16 (28th March 2022) - Lv, Guowei; Tian, Hongmiao; Shao, Jinyou; Yu, Demei
Abstract : A review about electrohydrodynamic patterning (EHDP), including origin, theoretical and numerical studies, pattern formation process, fabrication of hierarchical structures, aligning and ordering of the anisotropic polymers and perspective. Abstract : The free surface of a thin polymeric film is often unstable and deforms into various micro-/nano-patterns under an externally applied electric field. This paper reviews a recent patterning technique, electrohydrodynamic patterning (EHDP), a straightforward, cost-effective and contactless bottom-up method. The theoretical and numerical studies of EHDP are shown. How the characteristic wavelength and the characteristic time depend on both the external conditions (such as voltage, film thickness, template-substrate spacing) and the initial polymer properties (such as rheological property, electrical property and surface tension) is theoretically and experimentally discussed. Various possible strategies for fabricating high-aspect-ratio or hierarchical patterns are theoretically and experimentally reviewed. Aligning and ordering of the anisotropic polymers by EHDP is emphasized. A perspective, including novelty and limitations of the methods, particularly in comparison to some conventional patterning techniques, and a possible future direction of research, is presented.